Induction and Resuscitation of the Viable but Non-culturable (VBNC) State in Acidovorax citrulli, the Causal Agent of Bacterial Fruit Blotch of Cucurbitaceous Crops - Kan, Yumin; Jiang, Na; Xu, Xin; Lyu, Qingyang; Gopalakrishnan, Vinoj; Walcott, Ronald; Burdman, Saul; Li, Jianqiang; Luo, Laixin (Frontiers in Microbiology, 2019)
Acidovorax citrulli is a gram-negative bacterium that infects a wide range of cucurbits causing bacterial fruit blotch (BFB) disease. Copper-based compounds are the most widely-used chemicals for managing BFB and other bacterial diseases in the field. Many bacteria can enter a viable but nonculturable (VBNC) state in response to stress, including exposure to copper, and recover the culturability when favorable conditions return. The present study demonstrates that A. citrulli strain AAC00-1 is able to enter into the VBNC state by treatment with different concentrations of copper sulfate. It took 3 h, 5 d and 15 d for all viable cells to lose culturability upon exposure to copper sulfate concentrations of 50 μM, 10 μM and 5 μM, respectively. The VBNC A. citrulli cells regained culturability when the Cu2+ ions were removed by chelation with EDTA or by transfer of cells to LB broth, a cell-free supernatant from a suspension of AAC00-1, oligotrophic media amended with casein hydrolysate or watermelon seedling juice. We also found that the VBNC cells induced by Cu2+ were unable to colonize or infect watermelon seedlings directly, but that resuscitated cells recovered full virulence equivalent to untreated bacterial cells in the log phase. To the best of our knowledge this is the first report on the VBNC state in A. citrulli and the factors that facilitate resuscitation and restoration of pathogenicity.